Sequência didática como instrumento para a possível promoção do desenvolvimento do engajamento - Gomes, Aline Aparecida Miranda (Universidade Federal de São Carlos, 2021)
Engagement is a multifaceted construct and its study seeks to trace ways to improve the teaching-learning process. For this, it analyzes the student's development and their interactions with school and pedagogical activities, thus observing facilitating actions for its promotion, as well as their contributions and possibilities for development. The present qualitative, descriptive and bibliographical research, delimited by the question: “How to build a didactic sequence in the teaching of Natural Sciences that is supported by the construct of engagement considering the analysis of a corpus of selected academic works?”. This analysis will be done through the assumptions of the theoretical framework of Content Analysis proposed by Bardin (2011). As a contribution of this research, the construction of a didactic sequence in science education addressing the microorganism content will be carried out and intends to promote knowledge about the engagement construct and activities that promote its evidence.
Didactic sequence as an instrument for the possible promotion of development of engagement
Keywords: Engajamento; Ensino de ciências; Sequência didática; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM